Studi Struktur Biaya dan Penerimaan Usahatani Kelapa Sawit Swadaya Pasca Peremajaan Di Kecamatan Sungai Bahar Kabupaten Muaro Jambi - Mirawati Yanita; Ernawati HD; Napitupulu Dompak (Universitas Muhammadiyah Purwokerto, 2020)
Palm oil development provides benefits in increasing the income of smallholders and communities, where palm oil production becomes the raw material of the processing industry that creates added value in the country. However, the cost and revenue of palm oil farming is a consideration of smallholders in the implementation of replanting. This research aims to: (1) describe the oil palm farming in Sungai Bahar Sub-District of Muaro Jambi Regency (2) Analyze the cost structure and revenue of smallholder oil palm in Sungai Bahar Sub-district of Muaro Jambi Regency. The scope of this research area is Suka Makmur Village, Marga Mulya Village, Mekar Sari Village, Sungai Bahar District Muaro Jambi Regency. This research was conducted by a descriptive and quantitative method using an analysis of the cost structure and revenue of oil palm smallholders. The results showed a replanting palm oil farm area of 2.13 hectares with palm oil of 7 to 8 years and production of 18,170 Kg/Ha/year. The cost incurred is Rp 25,647,303/Ha/year, and the revenue amounts to Rp. 33,527,655/Ha/Year. In the future, although there is still a positive difference between the revenue and cost of farming after the replanting, smallholders are suggested better to optimize the resources as an alternative to increasing revenue to meet the needs.